RELASI SOSIAL KEKERABTAN DALAM UPACARA ADAT PERNIKAHAN DAYAK TAMAN DI DESA MALAPI KECAMATAN PUTUSSIBAU SELATAN KABUPATEN KAPUAS HULU - Sarani, Anggela Tiara Laraswati; Bahari, Yohanes; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the social relations of kinship in the traditional wedding ceremony of the Taman Dayak tribe and to find out the stages in carrying out the Taman Dayak traditional marriage in Malapi Village, South Putussibau District. The research method used is descriptive with a qualitative research form. The source of this research data is the traditional advice in Malapi Village. Data collection techniques in this study are through observation, interviews, recording and documentation. While the tools used in data collection are observation guides, interview guides and notebooks. The analysis in this study is presented in a qualitative descriptive form using 3 informants. The results of this study show the form of relations, while also showing that the implementation of Taman Dayak tribal marriages includes three stages, namely, the mananya' stage, the paloa' stage, and the sule' stage.